Consensus guidelines for the management of posterior fossa tumour for low- and middle-income countries - Hafiza Fatima Aziz,; Mohammad Hamza Bajwa,; Naureen Mushtaq,; Saqib Kamran Bakhshi,; Kaynat Siddiqui,; Saad Akhtar Khan,; Rabeet Tariq,; Muhammad Shakir,; Mehar Masroor,; Fatima Suleman,; Pakistan Brain Tumour Consortium: (Authors list at the end of the supplement),; Syed Ather Enam, (Journal of the Pakistan Medical Association, 2024)
The posterior fossa is a limited compartment therefore lesions compressing its structures can result in devastating outcomes. It can cause significant neurological deficit due to mass effect on critical structures and hydrocephalus. Due to the nature of the infratentorial region, urgent surgical intervention is often the first-line option. Surgical neuro-oncologists guide patients and caregivers through the course of this disease and to inform them about the various options for management and long-term outcome optimisation. There is currently conflicting data; however, institutional experiences can guide us towards achieving improvements in surgical outcomes and quality of life. Advances in molecular classifications coupled with highdose radiation treatment improve our capacity for improving overall survival in these patients. Common childhood tumours are ependymomas, medulloblastomas, and juvenile pilocytic astrocytomas, while adults often present with metastases, and less commonly, cerebellar haemangioblastomas and gliomas. This paper outlines management strategies with consideration for multidisciplinary care and resourcelimited settings. Keywords: Cerebellar neoplasms, medulloblastoma, caregivers, hemangioblastoma, astrocytoma, ependymoma, hydrocephalus, neuro-oncology, neurosurgery, brain tumour, posterior fossa.